Racial disparities in access to transplant for multiple myeloma: : reflections on the Brazilian healthcare system with local data - Alves Pereira, Cathia; Carvalho Barbosa Neves, Gabriela; Carolina de Oliveira, Isabella; Macedo, Thiago; Silva Bruno Barbosa, Guilherme; Savi, Giullio; Victor Piccolo Feliciano, João (Revista Uningá, 2025)
Multiple myeloma (MM) is a neoplasia whose treatment may include hematopoietic stem cell transplantation (HSCT). The literature points to racial disparities in access to HSCT, but information on this issue is scarce in Brazil. This study aimed to analyze the racial composition of patients subjected to autologous HSCT for multiple myeloma in a single Brazilian center, discussing access to treatment. A retrospective review was conducted considering HSCTs performed between 2014 and 2022 at a Brazilian academic center. The categorization adopted by the IBGE was used for white, pardo, and black patients. Variables such as age at the time of transplant and region of origin were evaluated. Data were presented through descriptive statistics. A total of 130 patients were included: 106 white (81.5%), 10 pardo (7.7%), and 14 black (10.8%). 71 were men (54.6%) and 59 were women (45.4%), with no significant differences among racial groups. The median age was 60 years for white and 53 years for black and pardo patients. Among the subgroups, white individuals from the Southeast, Midwest, and Northeast regions represented 76.4%, 17%, and 2.8%, respectively, while black and pardo patients represented 62.5%, 12.5%, and 20.8%. This study identified a white majority among patients subjected to HSCT for MM management in a single center. A deeper analysis of these differences is essential, as these findings may reflect phenomena within the Brazilian healthcare system. Discussing this issue is crucial for better understanding access to transplantation in light of factors that contribute to inequality in this vulnerable patient group.